Implementasi Pendekatan Restoratif dalam Penyelesaian Sengketa Medis Perspektif Manfaat Hukum - Putu Dian Ekawati; Dey Ravena; Tono Hadi Susiarno (Yayasan Studi Cendekia Indonesia (YSCI), 2023)
The doctor-patient relationship is a therapeutic transaction in which agreements are made based on best efforts to heal the patient. This relationship is called the inspaning verb tenis, and although it is not obvious from the result, it puts more emphasis on the effort made. The intention to help a patient to cure an illness may not always work, and may even lead to patient disability or death as a result of medical intervention, leading to medical disputes, disputes between patients and physicians, and criminal proceedings. This research is legal research using only secondary data such as literature research and library materials, that is, research using a prescriptive legal approach. The paradigm of restorative justice legal approaches should be used in resolving medical disputes. This is the value of justice and happiness, or the elements of sanctions and how to deal with them. Restorative justice policies, as provided for in the 1945 Constitution, are more beneficial, dignified and socially just for all parties, both victims and society and the state, compared to litigation settlement. We provide comprehensive problem-solving solutions.